1990
DOI: 10.1520/jfs12806j
|View full text |Cite
|
Sign up to set email alerts
|

Time Since Death and Decomposition of the Human Body: Variables and Observations in Case and Experimental Field Studies

Abstract: Much of the difficulty in determining the time since death stems from the lack of systematic observation and research on the decomposition rate of the human body. Continuing studies conducted at the University of Tennessee, Knoxville, provide useful information on the impact of carrion insect activity, ambient temperature, rainfall, clothing, burial and depth, carnivores, bodily trauma, body weight, and the surface with which the body is in contact. This paper reports findings and observations accumulated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
427
1
17

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(458 citation statements)
references
References 8 publications
13
427
1
17
Order By: Relevance
“…2 and discussed above, factors other than ADD play a role in the rate of decomposition. Differences in humidity, seasonal insect activity, possible bacterial infections prior to death and scavenger activity, for example, all have an influence and need to be further investigated [3,4,13,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…2 and discussed above, factors other than ADD play a role in the rate of decomposition. Differences in humidity, seasonal insect activity, possible bacterial infections prior to death and scavenger activity, for example, all have an influence and need to be further investigated [3,4,13,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…For cadaver decomposition under anaerobic conditions the optimum temperature range is 21°C to 38°C with very limited activity at temperatures below 4°C [2,3,32].…”
Section: Discussionmentioning
confidence: 99%
“…as temperature is considered the most important variable [10] and insects the most significant environmental decomposer [3]. The presence and developmental rates of insects will have a significant effect on the decomposition process.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that obese bodies lose body mass more rapidly due to liquefaction of body fats, than compared to skinny individuals [10]. They also found that bodies weighing more than 110 kg decompose much more rapidly than bodies weighing approximately 65 kg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation